Cruciferous Vegetables, Isothiocyanates, and Bladder Cancer Prevention. Issue 18 (29th August 2018) - Abbaoui, Besma; Lucas, Christopher R.; Riedl, Ken M.; Clinton, Steven K.; Mortazavi, Amir
Abstract: Bladder cancer is a significant health burden due to its high prevalence, risk of mortality, morbidity, and high cost of medical care. Epidemiologic evidence suggests that diets rich in cruciferous vegetables, particularly broccoli, are associated with lower bladder cancer risk. Phytochemicals in cruciferous vegetables, such as glucosinolates, which are enzymatically hydrolyzed to bioactive isothiocyanates, are possible mediators of an anticancer effect. In vitro studies have shown inhibition of bladder cancer cell lines, cell cycle arrest, and induction of apoptosis by these isothiocyanates, in particular sulforaphane and erucin. Although not yet completely understood, many mechanisms of anticancer activity at the steps of cancer initiation, promotion, and progression have been attributed to these isothiocyanates. They target multiple pathways including the adaptive stress response, phase I/II enzyme modulation, pro‐growth, pro‐survival, pro‐inflammatory signaling, angiogenesis, and even epigenetic modulation. Multiple in vivo studies have shown the bioavailability of isothiocyanates and their antitumoral effects. Although human studies are limited, they support oral bioavailability with reasonable plasma and urine concentrations achieved. Overall, both cell and animal studies support a potential role for isothiocyanates in bladder cancer prevention and treatment. Future studies are necessary to examine clinically relevant outcomes and define guidelines on ameliorating the bladder cancer burden. Abstract : There is mounting evidence that isothiocyanates, derived from cruciferous vegetables, show strong promise to prevent bladder cancer, specifically transitional cell carcinoma (TCC) of the urinary bladder.